Who are your best people? : how to find, measure and manage your top talent - Stuart-Kotze, Robin (Prentice Hall, 2008)
Many companies often ignore their in-house talent, believing that the only way to get the top people is to seek elsewhere. This book destroys the widely-accepted myth of a talent shortage and shows how you can unearth and value the hidden talent that already exists in your organisation.